2017
DOI: 10.35808/ersj/738
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Supervisory Board Cross-Membership and Supervisory Board Members' Expertise to the Disclosure of Supervisory Board's Report: Empirical Evidence from Indonesia

Abstract: This research aimed to determine the effect of Sharia Supervisory Board cross-membership and Sharia Supervisory Board members' expertise to the disclosure of Sharia SupervisoryBoard's report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 5 publications
0
15
0
1
Order By: Relevance
“…Likewise Nomran, Haron, & Hassan (2018) demonstrated that cross-membership has a positive relationship with the ROA performance of Islamic banks and that it can allow SSBs to monitor external companies and disseminate company information. However, Muda (2017) found that cross-membership did not significantly influence the disclosure of SSB compliance reports related to confidentiality and conflicts of interest, due to the fact that some Sharia supervisory councils that serve in several institutions will have special access to confidential information on relevant Islamic banks, which could have a negative impact if this were revealed to competitors.…”
Section: Dual Board Positionmentioning
confidence: 95%
“…Likewise Nomran, Haron, & Hassan (2018) demonstrated that cross-membership has a positive relationship with the ROA performance of Islamic banks and that it can allow SSBs to monitor external companies and disseminate company information. However, Muda (2017) found that cross-membership did not significantly influence the disclosure of SSB compliance reports related to confidentiality and conflicts of interest, due to the fact that some Sharia supervisory councils that serve in several institutions will have special access to confidential information on relevant Islamic banks, which could have a negative impact if this were revealed to competitors.…”
Section: Dual Board Positionmentioning
confidence: 95%
“…Inner model evaluation through the bootstrapping menu also generates T-statistics values that will be used to test the hypothesis. The criteria are T-statistic> 1.66 [3], [18], [26], [34] & [36]. The result of T-statistics value in the table path coefficients is presented in the following figure: Based on the above table the indirect effect produces coefficient of 0.005, smaller than 1.66 (α = 5%) then the decision of hypothesis testing reject H0 and accept the hypothesis Ha [37],.In addition to hypothesis testing through the bootstrapping menu that produces T-statistics, inner model evaluation is also done by reviewing the R-Square value [27], [28]& [29].…”
Section: A Resultsmentioning
confidence: 99%
“…Therefore, the Government Regulation will issue should describe more detailed concepts and provisions concerning the framework the medium term budget [6], [7] & [8]. However, without any strategic and framework medium-term programs that contain specific objectives, outcomes, and outputs and has a measurable target, it is impossible to develop a mediumterm budget framework and performance budgets [20], [21], [22], [23], [26] & [27] .…”
Section: Results a Results 1 Evaluation Of Structural Model (Innmentioning
confidence: 99%